Cerebral Oximetry during Out-of-Hospital Resuscitation: Pilot Study of First Responder Implementation. (21st June 2022) - Shin, Jenny; Walker, Robert; Blackwood, Jennifer; Chapman, Fred; Crackel, Joseph; Kudenchuk, Peter; Rea, Thomas
Abstract: Background: Anoxic brain injury is a common mode of death following out-of-hospital cardiac arrest (OHCA). We assessed the course of regional cerebral oxygen saturation (rSO2 ) at the outset and during first responder resuscitation to understand its relationship with return of spontaneous circulation (ROSC) and functional survival. Methods: We undertook a prospective observational investigation of adult OHCA patients treated by a first-responder EMS agency in King County, WA. Cerebral oximetry was performed using the SenSmart® Model X-100 Universal Oximetry System (Nonin Medical, Inc). We determined cerebral oximetry rSO2 overall and stratified according to ROSC and favorable survival status defined by Cerebral Performance Category (CPC) of 1–2. Results: Among the 59 OHCA cases enrolled, 47% ( n = 28) achieved ROSC and 14% ( n = 8) survived with CPC 1–2. On average, initial rSO2 cerebral oximetry was 41% and was not different at the outset according to return of spontaneous circulation (ROSC) or survival status. Within 5 minutes of first responder resuscitation, those who would subsequently achieve ROSC had a higher rSO2 than those who would not achieve ROSC (51% vs. 43%, p = 0.03). Among patients who achieved ROSC, those who would survive with CPC 1–2 had a higher rSO2 cerebral oximetry following ROSC than nonsurvivors (74% vs. 60%, p = 0.04 at 5 minutes post ROSC), a difference that was not evident in the minutes prior to ROSC (55% vs. 51% at 3 minutes prior to ROSC, p = 0.5). Conclusion: In this observational study, where first responders applied cerebral oximetry, higher rSO2 during the course of care predicted ROSC among all patients and predicted favorable survival among those who achieved ROSC. Future investigation should evaluate whether and how treatments might modify rSO2 and in turn may influence prognosis.